Application of Baylis-Hillman methodology in the construction of complex heterocyclic targets - Ganto, Mlungiseleli MacDonald (Rhodes University, Faculty of Science, Department of Chemistry, 2009)
Baylis-Hillman reactions using various aromatic aldehydes, activated alkenes and catalysts have been used to: - access an extensive range of poly-heterocyclic products;explore chemoselectivity; and optimise reaction efficiency. Chromone-3-carbaldehydes and chromone-2-carbaldehydes, prepared via Vielsmeier-Haack and Kostanecki-Robinson methodology, respectively, have been used as Baylis-Hillman substrates with four different catalysts, viz., 1,4-diazabicyclo[2.2.2]octane (DABCO), 3-hydroxyquinuclidine (3-HQ), imidazole and N',N',N',N'- tetramethylpropanediamine (TMPDA), and with methyl vinyl ketone (MVK), methyl acrylate, cyclic enones (2-cyclohexen-1-one, 2-cyclopenten-1-one and chromones) as activated alkenes. Reactions of the chromone- -carbaldehydes with MVK afforded dimeric Baylis-Hillman adducts when catalyzed by DABCO but when the same reactions were repeated using 3-HQ as catalyst, the dimeric products were accompanied by tricyclic Baylis-Hillman adducts. Use of excess MVK, however, led to mixtures of the normal Baylis-Hillman adducts and the tricyclic adducts "“ interestingly, with the apparent absence of the dimeric products. While reactions of chromone-3-carbaldehydes with methyl acrylate afforded the normal Baylis-Hillman adducts, the chromone-2- carbaldehydes produced, instead, rearrangement products, consistent with an earlier, single observation. Reactions of 2-nitrobenzaldehydes with cyclic enones using imidazole as catalyst afforded the normal Baylis-Hillman adducts, reductive cyclisation of the 2-cyclohexen-1- one and 2-cyclopenten-1-one adducts, using acetic acid and iron powder, afforded the corresponding quinoline erivatives. Treatment of cyclic enones with pyridine-2-carbaldehydes and quinoline-2-carbaldehydes using TMPDA as catalyst generally gave the expected Baylis-Hillman adducts. However, indolizine derivatives were isolated directly from Baylis-Hillman reactions involving pyridine-2-carbaldehydes and 2-cyclohexen-1-one. The remaining Baylis-Hillman adducts were cyclized to the corresponding indolizines by treatment with acetic anhydride both under reflux and under microwave-assisted conditions, the latter approach providing remarkably rapid and efficient access to the polycyclic products. Computer modelling studies have been conducted on selected polycyclic products at the Molecular Mechanics (MM), Quantum Mechanical (QM) and Density Functional (DFT) levels. The theoretical results have been used to calculate UV, IR and NMR absorption data, which have been compared, in turn, with the experimental spectroscopic data. Use has also been made of the estreNova NMR prediction programme and, generally, good agreement has been observed between the predicted and experimental spectroscopic data.
Keywords: Heterocyclic compounds -- Derivatives; Heterocyclic chemistry